Asuhan Kebidanan Komprehensif Pada Ny. “T” Di UPTD Puskesmas Babakan Kabupaten Cirebon Tahun 2024 - Al Faidah; Pipit Indra L (MEJORA Medical Journal Awatara, 2025)
The breastfeeding rate in Indonesia has declined, with only 48.6% of infants receiving breast milk within the first hour after birth in 2021, compared to 58.2% in 2018. This study aims to implement comprehensive midwifery care, covering pregnancy, labor, postpartum, newborn care, and contraception. The study subject, Mrs. T (G3P2A0) with a gestational age of 39-40 weeks, received care at Babakan Public Health Center from February to May 2024. A case study approach was used with a descriptive method through anamnesis, observation, and SOAP documentation. Interventions included two ANC visits, labor assistance, four postpartum visits, and three newborn care sessions. Complaints of pain during pregnancy were managed through health education. Labor occurred normally on March 4, 2024, at 04:50 AM WIB, delivering a healthy baby girl weighing 3,900 grams and measuring 51 cm in length. During the postpartum period, the mother experienced low breast milk production, which was addressed through breast care, oxytocin massage, and Oketani massage. Newborn care was carried out without complications. The mother chose an IUD as her contraceptive method. This comprehensive midwifery care is expected to enhance maternal understanding of pregnancy, labor, postpartum, newborn care, and family planning program.